Preoperative Degenerative Changes at the Medial Sesamoid-Metatarsal Joint Is Associated with Postoperative Patient-Reported Outcomes in Hallux Valgus - Sophie Kush BS; Stone R. Streeter BS; Brett D. Steineman PhD; Scott J. Ellis MD; Matthew S. Conti MD (Foot & Ankle Orthopaedics, 2024)
Introduction/Purpose: While hallux valgus (HV) is understood to be a triplanar deformity of the first metatarsal, less is known about the contribution of the sesamoid-metatarsal joint (SMJ) to pain and function. Osteoarthritis of the SMJ is frequently present in HV feet, with an incidence rate ranging from 32% to 81%. Following surgical correction, approximately 10% of HV patients remain dissatisfied, but factors affecting postoperative outcomes are poorly understood. The primary aim of our study was to describe the relationship between degenerative changes at the SMJ as measured on weightbearing CT (WBCT) scans and 1-year patient-reported outcome scores following a modified Lapidus procedure for correction of HV. We hypothesized that decreased joint space at the SMJ would affect postoperative patient-reported outcomes. Methods: This study included 48 consecutive patients who underwent a modified Lapidus procedure for HV, had preoperative and at least 5-month postoperative WBCT scans, and had preoperative PROMIS scores and at least 1-year postoperative PROMIS Physical Function (PF), Pain Interference, and Pain Intensity scores. For each patient, the first metatarsal and sesamoids on pre- and postoperative WBCT scans were segmented using Disior Bonelogic software and uploaded to Geomagic Design X to perform distancing mapping. The minimum and average distances between the first metatarsal head and medial sesamoid (medial-SMJ) for each patient pre- and postoperatively were calculated. Sesamoid subluxation was measured on WBCT scans using the grading system from 0 to 3 (Yildirim et al.). A simple linear regression model was used to investigate the correlations between minimum preoperative and postoperative medial-SMJ distances and 1-year postoperative PROMIS scores in patients with postoperative reduction of the sesamoids (grade 0). Results: Preoperatively, the mean minimum and average medial-SMJ distances were 0.76 ± 0.37 mm and 1.54 ± 0.33 mm, respectively. Postoperatively, the mean minimum and average medial-SMJ distances were 1.08 ± 0.25 mm and 1.73 ± 0.24 mm, respectively. Thirty-five of 48 patients had a complete reduction of the sesamoids. Lower preoperative minimum distances at the medial-SMJ were significantly correlated with worse 1-year PROMIS PF scores (r=0.405, P=0.016) (Figure 1). Similarly, lower preoperative minimum distances at the medial-SMJ were significantly correlated with worse 1-year PROMIS Pain Intensity scores (r=-0.350, P=0.039) but did not reach significance for 1-year PROMIS Pain Interference scores (r=-0.286, P=0.095). The postoperative minimum medial-SMJ distance was not correlated with 1-year PROMIS PF, Pain Interference, and Pain Intensity scores. Conclusion: In HV patients undergoing a modified Lapidus procedure with postoperatively reduced sesamoids, decreased joint space at the medial sesamoid-metatarsal head articulation was associated with worse 1-year postoperative function as measured by PROMIS PF scores and worse 1-year postoperative pain as measured by PROMIS Pain Intensity scores. In contrast, postoperative degenerative changes at the SMJ were not found to be associated with patient-reported outcomes. Our results suggest that pre-existing SMJ arthritic changes may affect postoperative outcomes and may be a source of dissatisfaction following HV surgery despite appropriate correction of the deformity. Figure 1. Preoperative medial sesamoid to the first metatarsal head minimum distance relative to 1-year PROMIS Physical Function, Pain Intensity, and Pain Interference scores. A simple linear regression demonstrates a significant association between preoperative medial sesamoid –metatarsal head minimum joint distance and 1-year PROMIS Physical Function (r=0.405, P=0.016) and Pain Intensity (r=‒0.305, P=0.039) scores.